Empirical models to describe the solar drying of S. Bartolomeu pears. - Guiné, Raquel (2013)
In Portugal, pears of the variety S. Bartolomeu (Pyrus communis L.) have been used to produce a traditional product named “pêra passa de Viseu”. These pears are dried at direct open air sun exposure, following a multi-step procedure. In the last years some investigation around this product and the production method has been carried out to better understand them and establish alternative production techniques. In the present work some study was carried out in order to find empirical models capable of describing the variation of relative weight loss along the solar drying of pears with some air properties (temperature and relative humidity) and also with some material properties (moisture content and total soluble solids content). Two kinds of software were used to estimate the parameters of the tested models, SigmaPlot and ODRPACK, and the results enabled us to conclude that the fittings obtained with both were consistent.